Effects of Diversity on Knowledge Sharing and Creativity of Work Teams: Status Differential Among Members as a Facilitator. Issue 3 (8th August 2019) - Sung, Sun Young; Choi, Jin Nam
ABSTRACT: We investigated a plausible intermediate process and a boundary condition that elaborates the diversity–team creativity relationship to address mixed findings on the relationship between diversity and creativity. Our analysis using multi-source data collected from 128 work groups showed that age diversity and functional background diversity had negative and positive effects, respectively, on knowledge sharing and subsequent team creativity. Moreover, the effects of the four diversity attributes (age, gender, functional background, and tenure) on knowledge sharing were all negative in groups with low status differential, whereas the same effects became significantly positive in groups with high status differential. This study demonstrates a mechanism through which group diversity facilitates team creativity based on the information processing view of diversity and the functional approach to social status.